1998
DOI: 10.3758/bf03199209
|View full text |Cite
|
Sign up to set email alerts
|

Pigeons’ memory for event duration: Differences between visual and auditory signals

Abstract: In Experiment 1,pigeons were trained to discriminate short (2 sec) and long (8 sec) durations of tone by responding to red and green comparison stimuli. During delay testing, a systematic response bias to the comparison stimulus correct for the long duration occurred. Tests of responding without the tone reduced accuracy on long-sample trials but not on short-sample trials suggesting that the pigeons were attending to the tone and not simply timing the total trial duration. The pigeons were then trained to mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 40 publications
(46 reference statements)
2
15
1
Order By: Relevance
“…Recal1that the pigeons in Group Dark-Dark pecked the samples significantly more than did the pigeons in Group LightDark. Choose-long effects of the kind found here have been reported in both rats (Santi, Weise, & Kuiper, 1995) and pigeons (Santi, Stanford, & Coyle, 1998) when samples involved durations of tone, but, to our knowledge, this is the first time such a bias has been reported in pigeons using visual sample durations.…”
Section: Retention Functionscontrasting
confidence: 45%
“…Recal1that the pigeons in Group Dark-Dark pecked the samples significantly more than did the pigeons in Group LightDark. Choose-long effects of the kind found here have been reported in both rats (Santi, Weise, & Kuiper, 1995) and pigeons (Santi, Stanford, & Coyle, 1998) when samples involved durations of tone, but, to our knowledge, this is the first time such a bias has been reported in pigeons using visual sample durations.…”
Section: Retention Functionscontrasting
confidence: 45%
“…The frequency of the tone was the same as that used in several previous studies on the timing of filled tone intervals in pigeons (Cheng & W. A. Roberts, 1989;W. A. Roberts, Cheng, & Cohen, 1989;Santi, Stanford, & Coyle, 1998). The intensity ofthe tone was 68 dB in one room and 60 dB in the other two rooms (as measured from the interior of the Plexiglas cage with a Radio Shack Digital Sound Level Meter 33-2055).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, when a delay was introduced after the sample stimulus, Santi et al (1998) found a choose-short effect when pigeons timed visual stimuli. This suggests that pigeons start timing at the onset of the visual signal and stop at the offset of the signal.…”
Section: Discussionmentioning
confidence: 99%
“…However, the modality of the event being timed also appears to play a role in the assessment of memory for event duration. Santi et al (1998) trained pigeons to match short and long durations of light to one set of color comparisons and the same durations of tone to a different set of color comparisons. During delay testing, choose-short errors occurred following light durations, but choose-long errors occurred following tone durations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation